Arguments for The Islamic Economics' Scientific Construction (Epistemological Review) - Muhammad Yafiz (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2021)
This essay seeks to provide an epistemological explanation of the scientific building of Islamic economics. The validity of Islamic economics as a body of knowledge that can be explained both rationally and religiously is also explained in this article through a number of arguments. A literature study strategy is used in the research method, which is qualitative research. Data gathered using library resources (library research) were simultaneously examined (descriptive analysis), i.e., the presentation of the data was done at the same time as the analysis. The results of this study explain that Islamic Economics as a discipline epistemologically is a discipline that can be accounted for scientifically by tracing the nature of Islamic economics, its sources and methods of acquisition as well as the validity and truth of Islamic economics.